Comparative Analysis of Pharmacopeial Requirements to Extem-poraneous Medicines - Galyna Melnik (Journal of Global Pharma Technology, 2020)
Abstract. The article presents a comparative analysis of pharmacopoeial requirements for extemporaneous medicines on the example of the articles of State Pharmacopoeia of Ukraine 2.0 “Nonsterile medicines made in pharmacies” and Guide for the Compounding Practitioner USP on Compounding “795” “Pharmaceutical Compounding – Nonsterile Preparations”. These articles have been shown to differ in structure and title, but many sections are close in content. It is established that State Pharmacopoeia of Ukraine contains, to date, a very limited list of general pharmacopoeial articles for individual extemporaneous dosage forms unlike USP. In this regard, it is necessary to expand and improve the basic regulatory documentation, including general articles of State Pharmacopoeia of Ukraine, in order to improve the quality of extemporaneous medicines.